The sociomotor role and its meaning in traditional sporting games: Socio-affective rejection in question - Zhaïra Ben Chaâbane; Carlos Mallén-Lacambra; Aaron Rillo-Albert; Cristòfol Salas-Santandreu; Felipe Menezes-Fagundes; Verónica Alcaraz-Muñoz; Miguel Pic; Rosa Rodríguez-Arregi; Pere Lavega-Burgués (PLoS ONE, 2025)
Purpose This study analyses the sociomotor dynamics of the traditional sporting game (TSG) Bear, Guardian and Hunters from the perspective of motor praxeology, exploring how players adjust their strategies according to the internal logic of the game and their socio-affective status. Method This is an observational study involving 10 university students, recording a total of 1,810 observational sequences during the game’s development. Variables such as type of striking and distance from the Bear were assessed, along with sociometric indices of rejection and their influence on motor decisions. Results The phases of the game condition players’ behaviour. In the initial phase, motor aggressiveness predominates; in the intermediate phase, a defensive strategy is adopted; and in the final phase, extreme prudence prevails. Players with higher levels of social rejection exhibit more aggressive behaviour, and the Hunters tend to distance themselves more from the Bear when the latter is marginalised. Conclusion This TSG provides a valuable educational setting for developing socio-affective relationships, managing motor aggressiveness, and fostering interpersonal relationships.